Incidence and prevalence of elite male cricket injuries using updated consensus definitions - Orchard JW; Kountouris A; Sims K (Dove Medical Press, 2016)
John W Orchard, Alex Kountouris, Kevin Sims National Cricket Centre, Cricket Australia, Brisbane, Australia Background: T20 (Twenty20 or 20 over) cricket has emerged in the last decade as the most popular form of cricket (in terms of spectator attendances). International consensus cricket definitions, first published in 2005, were updated in 2016 to better reflect the rise to prominence of T20 cricket.  Methods: Injury incidence and prevalence rates were calculated using the new international methods and units for elite senior male Australian cricketers over the past decade (season 2006–2007 to season 2015–2016 inclusive).  Results: Over the past 10 seasons, average match injury incidence, for match time-loss injuries, was 155 injuries/1,000 days of play, with the highest daily rates in 50-over cricket, followed by 20-over cricket and First-Class matches. Annual injury incidence was 64 injuries/100 players per season, and average annual injury prevalence was 12.5% (although fast bowlers averaged 20.6%, much higher than other positions). The most common injury was the hamstring strain (seasonal incidence 8.7 injuries/100 players per season). The most prevalent injury was lumbar stress fractures (1.9% of players unavailable at all times owing to these injuries, which represents 15% of all missed playing time).  Discussion: The hamstring strain has emerged from being one of the many common injuries in elite cricket a decade ago to being clearly the most common injury in the sport at the elite level. This is presumably in association with increased T20 cricket. Lumbar stress fractures in fast bowlers are still the most prevalent injury in the sport of cricket at the elite level, although these injuries are more associated with high workloads arising from the longer forms of the game. Domestic and international matches have very similar match injury incidence rates across the formats, but injury prevalence is higher in international players as they play for most of the year without a substantial off-season. Keywords: injury surveillance, incidence, prevalence, cricket, bowling